The Problem of Legal Protection for Human Rights Activists - Sulistyowati; Wahyu Nugroho; Umar Ma’ruf (Sociological Jurisprudence Journal, 2023)
The Constitution of the Republic of Indonesia of 1945, both in the preamble and torso, has clearly stated the protection of human rights, including human rights activists. This study aims to describe and examine the concept of the 1945 Constitution of the Republic of Indonesia as the Indonesian constitution, which mandates the state to protect human rights activists. The research method used is normative research with a qualitative analysis approach, with data collection carried out through literature studies. The results show that respect, protection, and guarantee of human rights are characteristics of the Indonesian legal state, especially after the amendment. However, because in more detail, the legal protection of human rights activists is only in the National Commission on Human Rights Regulations, not in a law or government regulations, the protection is still weak. Therefore, it cannot fulfill the rights and protect human rights activists as mandated in Article 27 paragraph (1), Article 28 paragraph (1), Article 28I paragraph (1), Article 28J paragraph (1), and article. 28J paragraph (4) of the Constitution of the Republic of Indonesia of 1945.